Super‐Bright Green Perovskite Light‐Emitting Diodes Using Ionic Liquid Additives. Issue 3 (15th January 2023) - Sadhukhan, Priyabrata; Kim, Min Seong; Baek, Sung‐Doo; Myoung, Jae‐Min
Abstract: Halide perovskites have potential for use in next‐generation low‐cost, high‐efficiency, and highly color‐pure light‐emitting diodes (LED) that can be used in various applications, such as flat and flexible displays and solid‐state lighting. However, they still lag behind other mature technologies, such as organic LEDs and inorganic LEDs, in terms of performance, particularly brightness. This lag is partly due to the insulating nature of the long‐chain organic ligands used to control the perovskite‐film morphology. Herein, a 1‐butyl‐3‐methylimidazolium tetrafluoroborate ionic liquid (IL) is incorporated as a potential additive with CsPbBr3 perovskite precursors, which results in a super‐bright green perovskite light emitting diode (PeLED) achieving a peak luminance of 3.28 × 10 5  cd m −2 only at a bias voltage of 6 V, with a peak external quantum efficiency of 13.75%. This achievement is the outcome of multirole support from IL that simultaneously enables superior control over the perovskite‐film morphology, passivates defects, modifies the band energy levels, and prevents ion migration. Hence, this work demonstrates IL as a novel alternative additive with the potential to outperform conventional long‐chain ligands in high‐performance PeLED device fabrication. Abstract : This article demonstrates the huge potential of ionic liquids as a novel and stand‐alone additive for high performance perovskite light‐emitting diodes. Ionic liquid has multirole effects on the perovskite layer including morphology control, band energy modification, defect passivation, and reduction of ion migration, which result in an impressive luminance of 3.28 × 10 5  cd m −2 with 13.75% external quantum efficiency.